Perspectives on regular and support class placement and factors that contribute to success of inclusion for children with ASD - Carter, Mark; Stephenson, Jennifer; Clark, Trevor; Costley, Debra; Martin, John; Williams, Katrina; Browne, Leah; Davies, Louise; Bruck, Susan (DISES, 2014)
For young children with autism spectrum disorder (ASD) in regular schools, ASD specific service delivery options include regular class placement with itinerant consultative support and support class placement. This study provided an examination of levels of parent, teacher and principal satisfaction with both regular class placement (n = 39) and a satellite support class option (n=35), which provides a more gradual transition into regular class. Given that regular class placement was the ultimate goal for children enrolled in the study, factors that either facilitated or acted as barriers to successful inclusion were examined for those children currently in regular classes. There were relatively high levels of parent, teacher and principal satisfaction with both satellite support class and regular class placement for children with ASD, with higher levels of parental satisfaction with satellite support placement. Across all respondents, the most frequently identified facilitating factors were related to teaching practices and skills. In contrast, barriers identified were generally related to child characteristics. A number of suggestions for future research are offered.